Síndrome Rendu-Osler-Weber como causa de sangrado digestivo alto. Presentación de un caso y revisión de la literatura - Rodolfo Morales Valdés; Mario Orlando Hernández Cubas; Mailyn Acosta Álvarez; Javier Cruz Rodríguez; Joel Ramos Rodríguez; Yohny Calle Caspa (Revista Finlay)
Hereditary hemorrhagic telangiectasia is an autosomal dominant disorder of the walls of the blood vessels that become tortuous and dilated. Clinically, patients with this disease develop recurrent bleeding, which may occur spontaneously or following minor trauma. We present the case of a 68-year-old male patient who was admitted due to an upper gastrointestinal bleeding and diagnosed with Rendu-Osler-Weber disease. After application of treatment, the patient recovered and was discharged from the hospital.